Exploring the Benefits of Herbal Medicine Composite 5 (HRMC5) for Skin Health Enhancement - Rira Ha; Won Kyong Cho; Euihyun Kim; Sung Joo Jang; Ju-Duck Kim; Chang-Geun Yi; Sang Hyun Moh (Current Issues in Molecular Biology)
The skin, as the body’s largest organ, is vital for protecting against environmental stressors, regulating temperature, and preventing water loss. Here, we examined the potential of a mixture of five traditional Korean herbal extracts—Cimicifuga racemosa, Paeonia lactiflora, Phellodendron amurense, Rheum rhaponticum, and Scutellaria baicalensis—referred to as herbal medicine composite 5 (HRMC5) for enhancing skin health and managing menopausal symptoms. High-performance liquid chromatography identified 14 bioactive compounds, including flavonoids, phenolic acids, anthraquinones, and alkaloids. In vitro studies revealed an optimal concentration of 0.625 g/L for cell survival and UV protection, with the mixture demonstrating significant wound-healing properties comparable to epidermal growth factor. HRMC5 exhibited anti-inflammatory effects by downregulating COX2 expression and upregulating the key skin barrier proteins. A 4-week clinical trial involving 20 postmenopausal women showed significant improvements in skin redness, hemoglobin concentration, and skin moisture content. Visual analog scale assessments indicated substantial reductions in facial flushing severity and the associated sweating. The topical application of HRMC5 cream offered potential advantages over ingested phytoestrogens by reducing the systemic side effects. These findings suggest that HRMC5 is a promising non-invasive treatment for vasomotor symptoms in menopausal women and overall skin health, warranting further research on its long-term efficacy and safety in larger populations.